Des musulmanes ouest-africaines au Québec : entre subversion et conformité - Traoré, Fatoumata Diahara (Pluralismes (Presses de l'Université de Montréal), 2019)
Ce livre explore les diverses facettes de l'islam tel qu'il est vécu, raconté et transformé par des immigrantes ouest-africaines vivant au Québec. Leurs trajectoires migratoires recoupent parfois des trajectoires religieuses, dans un contexte où les savoirs religieux officiels font l'objet d'une appropriation mitigée, et l'islam se trouve dès lors réinventé et reconfiguré.Cet ouvrage présente ainsi des formes d'islamité ancrées dans de nouvelles façons d'être musulman, dans une mondialité de plus en plus déterritorialisée. Les immigrantes ouest-africaines réconcilient donc l'islam "authentique" avec des pratiques considérées comme illicites par l'orthodoxie, par exemple la divination et les rituels magiques. Elles proposent de ce fait de nouvelles constructions féminines du sacré, en marge d'un monde dominé par les hommes, ce qu'expose avec nuance et sensibilité l'autrice dans ce petit livre tout en confidences
Keywords: afrique; afrique de l'ouest; amériques; anthropologie; care; cours; discipline; femmes immigrantes; histoire et politique; musulmanes; québec; religion; régions géographiques; sciences humaines; soc1061; sociologie; thématiques

Structural competency in emergency medicine services for transgender and gender non-conforming patients - Willging, Cathleen; Gunderson, Lara; Shattuck, Daniel; Sturm, Robert; Lawyer, Adrien; Crandall, Cameron (Social Science & Medicine, 2019)
In this formative qualitative research, we draw upon the concepts of structural vulnerability and structural competency to examine how transgender and gender non-conforming (TGGNC) patients and healthcare personnel experience service delivery in Emergency Departments (EDs), and how this experience can be improved upon. Between October 2016 and June 2017, we undertook 31 semi-structured interviews with TGGNC patients (n = 11) and physicians (n = 6), nurses (n = 7), and non-clinical staff (n = 7) in four community-based EDs in New Mexico. Our iterative coding and analysis process resulted in eight sets of findings: (1) reasons why TGGNC patients seek care from EDs; (2) perceptions about and experiences of TGGNC patients; (3) relevance of gender identity and sex at birth; (4) bureaucracy and communication; (5) spatial considerations; (6) preparing providers and staff to care for TGGNC patients; (7) the lack of resources for structural prescriptions; and (8) respect, humanity, and sameness. Findings suggest that structural issues adversely impact the health and wellbeing of TGGNC patients and service-delivery practices in the ED. We describe study implications for training ED personnel and modifying this practice setting to prevent delayed care and ensure appropriate services for TGGNC patients in need of structurally competent emergency medicine.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; amériques; anthropologie; discipline; personnes trans*; projet charge mentale; périodes historiques; régions géographiques; santé; sciences humaines; service d'urgences; thématiques; états-unis